Success and failure in limited war information and strategy in the Korean, Vietnam, Persian Gulf, and Iraq Wars - Bakich, Spencer D. (The University of Chicago Press, 2014)
Common and destructive, limited wars are significant international events that pose a number of challenges to the states involved beyond simple victory or defeat. This book investigates a crucial and heretofore ignored factor in determining the nature and direction of limited war: information institutions